Growth Rate of Green Turtle Hatchlings (Chelonia mydas) With Different Feeding inConservation Lab Banyan TreeResort Lagoi Bintan Island - Elvi Hartati Anggraini; Syafruddin Nasution; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in October-December 2015 in Conservation labBanyan Tree Resort Lagoi Bintan Riau Islands Province. The purpose of this study was to determine the growth rate of green turtle hatchlings (C. mydas) with different feeding. This study is using anexperiment method by giving three variation of food,consistedof squid, fish and shrimp. There was one factor oftreatment, with three levels and three replications. Growth rate and mortality of each treatment were measured every two weeks by census. The results of the study has shown the highest growth rate of hatchlings was feed on squid (Loligo sp), followed by feed on fish (Lutjanus campechanus) and shrimps (Panaeus merguensis). Key words : Chelonia mydas, growth, feeding, Banyan Tree Resort, Bintan